Preservation of Traditions and Economic Development of the Sayyid Traditional Community in Cikoang - Faisal, Muhamad; Halim, Abdul; Roslianah; Nashar (Jurnal Pallangga Praja (JPP), 2025)
The purpose of this study was to determine the economic activities of the Sayyid indigenous community, not only as an effort to maintain the uniqueness of their customs that require high costs but also in pursuing the ideals of achieving a better standard of living and government policies both national, regional, and local/village related to the economic development of the Sayyid indigenous community. This study is descriptive and uses qualitative research methodology to collect information. Data were collected through interviews, observations and documentation. Data analysis includes data reduction, data display and drawing conclusions (verification). The results of the study indicate that the economic activities of the Sayyid indigenous community are no different from those of society in general, they work not only to get a better quality of life, but also in order to preserve their traditional traditions. The village government policy is not only to build road infrastructure in the context of economic development in Cikoang Village, but also to provide equipment to the Sayyid indigenous community in order to support their economic activities.